Projecting the Suicide Burden of Climate Change in the United States. (10th May 2022) - Belova, Anna; Gould, Caitlin A.; Munson, Kate; Howell, Madison; Trevisan, Claire; Obradovich, Nick; Martinich, Jeremy
Abstract: We quantify and monetize changes in suicide incidence across the conterminous United States (U.S.) in response to increasing levels of warming. We develop an integrated health impact assessment model using binned and linear specifications of temperature‐suicide relationship estimates from Mullins and White (2019), in combination with monthly age‐ and sex‐specific baseline suicide incidence rates, projections of six climate models, and population projections at the conterminous U.S. county scale. We evaluate the difference in the annual number of suicides in the U.S. corresponding to 1–6°C of warming compared to 1986–2005 average temperatures (mean U.S. temperatures) and compute 2015 population attributable fractions (PAFs). We use the U.S. Environmental Protection Agency's Value of a Statistical Life to estimate the economic value of avoiding these mortality impacts. Assuming the 2015 population size, warming of 1–6°C could result in an annual increase of 283–1, 660 additional suicide cases, corresponding to a PAF of 0.7%–4.1%. The annual economic value of avoiding these impacts is 2 billion–3 billion (2015 U.S. dollars, 3% discount rate, and 2015 income level). Estimates based on linear temperature‐suicide relationship specifications are 7% larger than those based on binned temperature specifications. Accounting for displacement decreases estimates by 17%, while accounting for precipitation decreases estimates by 7%. Population growth between 2015 and the future warming degree arrival year increases estimates by 15%–38%. Further research is needed to quantify and monetize other climate‐related mental health outcomes (e.g., anxiety and depression) and to characterize these risks in socially vulnerable populations. Plain Language Summary: We project the effects of climate change on mental health in the U.S. through the end of the century by looking at potential changes to suicide rates. Separately, we estimate the U.S. population's potential willingness to pay to avoid the projected suicide impacts and to contextualize additional costs of suicide prevention. We show that, depending on increases in global temperatures, suicides in the U.S. could increase by an additional 283–1, 660 cases annually. This represents a 0.7%–4.1% increase from the average 1999–2019 suicide rate and 2015 population. The largest impacts are observed in regions with higher average suicide rates from 1999 to 2019 (Northwest, North Central, and South), higher population density (Northwest, Northeast, Midwest, and South), and the largest increases in temperature and decreases in precipitation (Midwest, North Central, Northeast, and South). We estimate the annual economic value of avoiding these additional suicides could range from 2 billion to 3 billion (2015 dollars and 3% discount rate). The mental health burden of climate change is likely much greater than the impacts we report, as our analysis does not include more common indicators of poor mental health, such as depression or anxiety. Key Points: We project changes in suicide incidence across the conterminous United States (U.S.) in response to warming by using six climate models 1–6°C of warming could result in 283–1, 660 additional suicide cases annually (2015 U.S. population), a 0.7%–4.1% increase from baseline The greatest proportional impacts are seen in the Midwest, the North Central, the South Central, and the Southeast regions